THE USE OF AUTHENTIC MATERIALS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Shamsuddinova Diyoraxon Yorqinbek qizi; Mirzaazizova Farangiz (TADQIQOTLAR, 2025)
Abstract The integration of authentic materials in English as a Foreign Language (EFL) classrooms  has  garnered  significant  attention  for  its  potential  to  enhance  language acquisition. Authentic materials—resources created for native speakers—offer learners exposure  to  real-life  language  use,  cultural  nuances,  and  contextualized communication.  This  article  examines  the  benefits  and  challenges  of  employing authentic  materials  in  EFL  instruction,  drawing  on  recent  studies  and  pedagogical insights. It also provides practical strategies for effective implementation, aiming to guide  educators  in  enriching  their  teaching  practices  and  fostering  learners’ communicative competence.